Improvement of artistry at the qualified sportswomen in rhythmic gymnastics - Alla Mullagildina (Слобожанський науково-спортивний вісник, 2016)
Purpose: to define influence of means of modern choreography on artistic abilities of the qualified sportswomen in rhythmic gymnastics. Material & Methods: art-aesthetic requirements by the technique of V. S. Avanesov were defined at eight candidates of master of sports, choreographic priorities were found out by means of questioning and conversation, the level of coordination abilities of gymnasts by motive tests was defined. Results: Classes by choreography, communication with music are priority in art- aesthetic needs of gymnasts. Most of gymnasts gave their advantage to the use of techniques of contemporary dance and jazz modern from means of modern choreography. Conclusions: the level of musically-rhythmical preparedness, coordinate movements by different parts of body, expressiveness of movements improved considerably under the influence of means of modern choreography at gymnasts that promoted the improvement of artistry of sportswomen.